Financial Performance and Share Price of PT Barito Renewables Energy Tbk Post-Acquisition - Nurfaiza, Anggita; Fuada, Nurul (Amsir Accounting & Finance Journal, 2025)
This study aims to analyze the effect of fundamental performance changes on stock price movements in PT Barito Renewable Energy Tbk. (BREN) before and after the acquisition. The data used includes financial ratios in the form of Return On Equity (ROE), Debt to Asset Ratio (DAR), and Current Ratio (CR) from the quarter before and after the acquisition as well as historical data on stock price movements in the same period, the results of the study show that after the acquisition ROE had decreased but increased again and remained stable and the current ratio (CR) decreased. Despite the improvement in fundamental performance, the stock price remains highly volatile and subject to sharp declines. This shows that stock price movements are not entirely influenced by fundamentals but also by market sentiment.